Hasil Tangkapan Ikan Demersal Dengan Pancing Dasar Di Teluk Nalahia, Maluku Tengah - Thobias Sairmau; Abraham M. O. Sabandar; B G Hutubessy (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2023)
Small scale fisheries are commonly multi-species fisheries practice which targeting on varied species and sizes that provide better income using multi-gear. Yet, tropical fisheries management more focuses on single-species management including studies to support the management. In this study, we analyzed the catch of hand line using multi-species approachment, size abundance spectrum. Hand line with hook size 13 and 15, 64 individual were collected during 10 trips of fishing at Nalahia Bay. Represented of 34 species from 15 family, the catch of hand line has ecological function from herbivores to piscivores, 2 to 4.5 of trophic level. Abundance size spectrum of hand line showed that Nalahia Bay comprehends high diversity of demersal fish and hand lines exploit proportionally to the available productivity.